Features of modern Turkish legal language and historical formation of law terms (Journal of Oriental Studies, 2018)
Legal language is the most complicated and hard to understand version of the standard languagedue to its lexicon, terminology as well as syntactical features. Therefore, the use, comprehension andinterpretation of this language by non-specialists is very difficult. Turkish, as a language of science, hasreached today the competence to express the most complicated legal relations because of its vocabularyand terminological basis. This article primarily deals with the terminological basis and vocabulary of themodern Turkish legal language also taking into consideration their historical formation.